Penguatan Manajemen Usaha dan Inovasi Digital UMKM Serta Pendidikan Kreatif Untuk Masyarakat Desa Mandiri - Sutrisna, Endang; Putri, Armelia; Yani, Mutia Rahma; Silaen, Cici Febrina; Dezka, Viola Fauziah; Putri, Nazhifah Novenda; A, Adeliya; Mansiz, Muhammad Ilhan; S, Summayah; Mulia, Zelan Putra; Muhammad, Dzaky Marie; Yewanda, Gefano; Syah, Ajian (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The village of Sialangrampai, located in Kulim District, Pekanbaru City, is an area with strategic potential in agriculture, UMKM development, and Malay cultural preservation. However, UMKM in the region still face various obstacles, including irregularities in financial record-keeping, limited marketing access, and low utilization of digital technology. To address these issues, the MBKM FISIP Riau University Real Work Lecture Program (KUKERTA) was implemented for 50 days, from June 23 to August 12, 2025, with the main objectives of increasing UMKM capacity, digital literacy, creative education, and strengthening local culture. The program implementation methods included surveys and problem mapping, seminars, training, mentoring, and field activities. The results included the registration of 10 UMKM on Google Maps, improved product branding, financial literacy seminars attended by dozens of business owners, tutoring activities for 20 children, leadership training for 35 students, and Zapin dance training involving 30 children. In addition, this program also produced social initiatives in the form of providing trash bins, installing educational information boards, and social-religious activities. The impact of this program included increased digital skills among the community, increased awareness of business management among business owners, increased participation in education, and the preservation of Malay culture. With the active involvement of the community, this activity showed that the synergy between universities, communities, and the government plays an important role in realizing sustainable empowerment.